La práctica artística en contextos de dramas sociales - Diéguez, Ileana (Latin American Theatre Review, 2011)
Using various examples of contemporary installation art, this essay explores questionsof social practices, liminality, absence, and mourning. Borrowing theories from Didi-Huberman, Victor Turner, Jesús Martín-Barbero, Giorgio Agamben, and others, the authordiscusses the role of imágenes de crisis created by artists such as Doris Salcedo, Erika Diettes,Teresa Margolles, and Ambra Polidori in providing a site for mourning within a setting ofextreme social conflict and disintegration. In places where disappearance is the norm, thingslike clothing and personal belongings perform a metonymic function in conveying the agonisticrelation between image and absence. Turner’s notions of social drama and liminality, inparticular, provide a paradigm that allows us to reevaluate the relationship that forms amongrite, culture, and art during times of intense social disequilibrium. (JEB, article in Spanish)